(E)-3-[4-(Decyloxy) phenyl]-1-(4-hydroxyphenyl) prop-2-en-1-one - Ibrahim, Abdul Razak; Fun, Hoong-Kun; Zainab, Ngaini; Norashikin Irdawaty, Abd Rahman; Hasnain, Hussain (International Union of Crystallography, 2009)
In the title compound, C25H32O3, the enone group adopts an s–cis conformation. The alkoxy unit is nearly planar and is in a trans conformation. The two benzene rings make a dihedral angle of 18.87 (9)°. In the crystal structure, molecules are linked into chains running along the a axis by intermolecular O—H⋯ O hydrogen bonds involving the hydroxy and keto groups. The chains are crosslinked along the b axis via C—H⋯ O hydrogen bonds, forming a two-dimensional network parallel to the ab plane.